How Plural is Pluralism? An Exploration of the Approach to Religious Pluralism in the Irish Primary Education System: A perspective through the lens of ERB and Ethics. - Conroy, Hilary (My University, 2019)
This study examines a sample of written submissions contributed by various stakeholders to the NCCA's consultation process, for the proposed implementation of a common curriculum in Education about Religion and Beliefs (ERB) and Ethics. Due to results gathered from the consultation process, the implementation of this new curriculum ultimately failed. Using thematic analysis various submissions were analysed in order to gain an insight into the public's views and opinions on the attempt made by the DES and NCCA to accommodate religious diversity and promote religious pluralism in Irish primary schools. The literature review chapter examines the relevant literature that was used to support and develop the rationale behind the ERBE curriculum, and suggests that a pervasive issue exists in relation to the provision of religious education in Ireland, particularly with regard to denominational schools. Interestingly, results from the analysis of data presented in the findings and discussion chapter, revealed a contradicting response from the general public. Although some agreed with the idea behind the proposed curriculum, the majority of respondents opposed it, expressing concerns surrounding both the curriculum and the consultation process. Respondents raised questions in relation to the accuracy of the NCCA's portrayal of Irish primary schools, the plural nature of the proposed curriculum, the approach to ethics education outlined in the proposals, limitations of the consultation process and finally expectations for teachers and pupils. From this, the researcher was able to draw various conclusions and recommendations that reveal and highlight the significantly complex nature of religious pluralism.
Professional Masters of Education
Keywords: Research Subject Categories; Education about Religion and Beliefs (ERB) and Ethics.; Religious diversity.; Religious pluralism.; Provision of religious education in Ireland